EXPLORING THE USE OF YOUTUBE VIDEOS WITH TEXTS AND WITHOUT TEXTS IN TEACHING LISTENING TO BEGINNER EFL STUDENTS - Amalia, Najwa Rizki; Purmasari, Siti Fatimah; Asri, Diar Mukti; Ramadhanti, Nisrina Farida; Ningrum, Cahaya; Syahid, Abdul (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to explore the use of YouTube videos, both with and without subtitles, in teaching listening skills to beginner-level EFL learners. The research is motivated by the evolution of digital technology, which provides new opportunities in language learning, particularly through video media that integrates audio, visual, and textual elements. A quasi- experimental method with a pretest-posttest nonequivalent control group design was employed. The subjects consisted of 73 8th-grade students at Berkah Integrated Junior High School, divided into two groups: an experimental class using videos with subtitles and a control class using videos without subtitles. Data were collected from the results of the pretest and posttest, analyzed using descriptive statistics and an independent t-test at a 0.05 significance level. The results indicated no statistically significant difference between the two groups (t = –1.720; p = 0.090). However, descriptively, the group without subtitles showed an increase in scores, while the group with subtitles experienced a slight decrease. This finding suggests that the use of subtitles might increase the cognitive load for beginner students as they have to divide their attention between reading the text and listening to the audio. Conversely, videos without subtitles allow students to fully focus on aural input. Therefore, the application of subtitles should be adjusted according to students' proficiency levels to avoid hindering the comprehension process. ABSTRAKPenelitian ini bertujuan untuk mengeksplorasi penggunaan video YouTube dengan teks (subtitle) dan tanpa teks dalam pengajaran keterampilan menyimak (listening) bagi siswa EFL tingkat pemula. Latar belakang penelitian ini berangkat dari perkembangan teknologi digital yang membuka peluang baru dalam pembelajaran bahasa, salah satunya melalui media video yang memadukan unsur audio, visual, dan teks. Metode yang digunakan adalah quasi- eksperimen dengan desain pretest-posttest nonequivalent control group. Subjek penelitian terdiri atas 73 siswa kelas VIII di Berkah Integrated Junior High School yang dibagi menjadi dua kelompok: kelas eksperimen menggunakan video dengan teks dan kelas kontrol menggunakan video tanpa teks. Data diperoleh dari hasil pretest dan posttest yang dianalisis menggunakan statistik deskriptif dan uji-t independen dengan taraf signifikansi 0,05. Hasil penelitian menunjukkan bahwa tidak terdapat perbedaan signifikan antara kedua kelompok (t = –1.720; p = 0.090). Namun, secara deskriptif, kelompok tanpa teks menunjukkan peningkatan skor, sedangkan kelompok dengan teks mengalami sedikit penurunan. Temuan ini mengindikasikan bahwa penggunaan subtitle dapat menambah beban kognitif bagi siswa pemula karena mereka harus membagi perhatian antara membaca teks dan mendengarkan audio. Sebaliknya, video tanpa teks memungkinkan siswa fokus pada input pendengaran secara penuh. Dengan demikian, penggunaan subtitle sebaiknya disesuaikan dengan tingkat kemahiran siswa agar tidak menghambat proses pemahaman.